(untitled) (Vietnam Journal of Community Medicine, 2025)
Governance effectiveness in Vietnamese public hospitals is currently influenced by numerous factors, particularly amidst the implementation of the Law on Medical Examination and Treatment and the ongoing digital transformation within the healthcare sector. Identifying and analyzing these influencing factors is crucial for enhancing service quality and fostering the sustainable development of the public healthcare system. Objective: To identify and analyze the factors affecting governance effectiveness in Vietnamese public hospitals within a rapidly evolving legal and technological landscape. Methodology: This study employs a mixed-methods approach (qualitative and quantitative), grounded in modern governance theories. It combines analysis of reports from the Ministry of Health with empirical surveys conducted at several public hospitals. Results: The study identifies five main groups of factors influencing governance effectiveness: (1) Professional and leadership capabilities of the management team; (2) The extent of IT application and digital transformation; (3) Financial mechanisms and financial autonomy capabilities; (4) The policy system and internal governance model; and (5) Organizational culture and employee engagement. Conclusion: These identified factors are closely intertwined with governance effectiveness in public hospitals. Based on the survey findings, the study proposes several policy recommendations aimed at enhancing governance capacity, improving the quality of healthcare services, and promoting the sustainable development of public hospitals in Vietnam.